Locke’s Atomic Theory of Ideas: Implications for Human Understanding - Ibrahim, Adekunle A.; Ihehiulor, Chidioziri O.; Nkanta, Ikemesit J. (NIU Journal of Humanities, 2026)
This paper examines Locke’s atomic theory of ideas and its implications for human understanding. The question “how is objective knowledge possible?” marked the dividing line between rationalism and empiricism in the modern period of philosophy. Rationalism on the one hand upholds the doctrine of innate ideas which claims that man possesses certain natural intellectual properties that exist prior to experience and provides privileged access to reality. Empiricism on the other hand countered with the opposing thesis that all genuine knowledge is derived from sense experience. As the chief speaker of the empiricists, Locke presents an atomic theory of ideas which holds that there are no such things as ideas before experience. He maintains that all ideas are products of experience and serve as building blocks of human knowledge. By so doing, Locke reduces the entirety of human knowledge structure to a collection of ideas derived from sense experience. Locke’s position has far reaching implications for human understanding as it addresses the foundation, structure and extent of human knowledge. In view of this, this paper through the use of philosophical methods of analysis and criticism examines Locke’s theory of ideas and its implications for human understanding. Keywords: Rationalism, Empiricism, Mind, Innate Ideas and Sense Experience